Increasing imperative of the intercultural education in European policies, initiatives and actions - Iryna Sikorska (Transformation, Integration and Globalization Economic Research (TIGER), 2021)
Through increasing cultural diversity of European countries education in general and higher education in particular become the constructive force to promote social cohesion and integration. The European higher education policies have manifested the increasing attention towards importance of intercultural learning at all levels of education including higher education. In the research the major EU policy-related documents, initiatives, programmes and organizations responsible for education policies are analyzed through introducing of the key themes and priorities connected with development of intercultural learning. The chronological scope of the study covers the last twenty-year period due to the enormous changes occurred in the field of higher education under increasing multicultural perspective in Europe.
Keywords: 330; European education policies; Higher education; Intercultural education